VirtualSense: A Java-Based Open Platform for Ultra-Low-Power Wireless Sensor Nodes. (8th November 2012) - Lattanzi, Emanuele; Bogliolo, Alessandro
Abstract : Idleness has to be carefully exploited in wireless sensor networks (WSNs) to save power and to accumulate the energy possibly harvested from the environment. State-of-the-art microcontroller units provide a wide range of ultra-low-power inactive modes with sub-millisecond wakeup time that can be effectively used for this purpose. At the same time they are equipped with 16-bit RISC architectures clocked at tens of MHz, which make them powerful enough to run a Java-compatible virtual machine (VM). This makes it possible to bring the benefits of a virtual runtime environment into power-constrained embedded systems. VMs, however, risk to impair the effectiveness of dynamic power management as they are seen as always-active processes by the scheduler of the operating system in spite of the idleness of the threads running on top of them. Avoiding to keep sensor nodes busy when they could be idle is mandatory for the energetic sustainability of WSNs. While most of the tasks of a sensor node are inherently event-driven, the functioning of its hardware-software components is not, so that they require to be redesigned in order to exploit idleness. This paper presents VirtualSense, an open-hardware open-source ultra-low-power reactive wireless sensor module featuring a Java-compatible VM.